Estimating the domestic determinants of foreign direct investment flows in Malaysia : evidence from cointegration / Siti Nabila Amran - Amran, Siti Nabila (Faculty of Business and Management, 2014)
Some studies have been done on Foreign Direct Investment (FDI) which defining and explaining on how it will work. The effect that FDI cause to a country will also be discuss in this section. After that, the study is narrowed down to the chosen country which is Malaysia. In this section, problem statement regarding the FDI in Malaysia and the independent variable which is exchange rate, inflation rate, economic growth, export of good & services and FDI China will also be introduced. An explanation of the dependent and independent variables is provided and this study is to discover the relationship of the variables mentioned.